Dante : Contemporary Perspectives - Iannucci, Amilcare A. (Book collections on Project MUSE., 1997)
Dante: Contemporary Perspectives gathers recent and newly commissioned articles on Dante Alighieri (1265-1321), whose epic the Divine Comedy, is one of the landmarks of world literature. The essays in this volume probe current critical assumptions about the celebrated Italian poet, literary theorist, moral philosopher, and political theorist. Dante's attitude towards poetic authority and language comes under scrutiny in several essays, while others examine his political thought and his views on women and gender. Several articles focus exclusively on the Divine Comedy, and, in particular, on its distinctive textual characteristics. There are new readings of two of the Divine Comedy's most important episodes - those of Paolo and Francesca, the Earthly Paradise, and Ulysses - whose significance extends far beyond their immediate contexts. These essays bring into focus Dante's bold narrative innovations and reflections on literature and history.